Radiotherapy enhances laser palliation of malignant dysphagia: a randomised study. - Sargeant, I R (1997)
BACKGROUND/AIMS: A major drawback of laser endoscopy in the palliation of malignant dysphagia is the need for repeated treatments. This study was designed to test whether external beam radiotherapy would reduce the necessity for repeated laser therapy. PATIENTS/METHODS: Sixty seven patients with inoperable oesophageal or gastric cardia cancers and satisfactory swallowing after initial laser recanalisation were randomised to palliative external beam radiotherapy (30 Gy in 10 fractions) or no radiotherapy. All patients underwent a 'check' endoscopy five weeks after initial recanalisation and were subsequently reendoscoped only for recurrent dysphagia, which occurred in 59 patients. RESULTS: Dysphagia was relieved equally well in both groups and the improvement was maintained with further endoscopic treatment. The initial dysphagia controlled interval and the duration between procedures required to maintain lifelong palliation (treatment interval) increased from five to nine weeks (median) in the radiotherapy group (p < 0.01 both parameters). Radiotherapy was well tolerated in all but three patients. One perforation occurred and two fistulae opened after dilatation in patients who received radiotherapy. CONCLUSION: Additional radiotherapy reduces the necessity for therapeutic endoscopy for a patient's remaining life. It has an important role in relatively well patients who are likely to survive long enough to benefit.